Job preferences of Japanese global health personnel: results from a discrete choice experiment - Eriko Jibiki; Timothy Bolt; Tomohiko Sugishita (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background The disintegration of the boundary between global and national health due to the emergence of global health issues, such as COVID-19, led to the increasing need to nurture global health experts so as to strengthen global and national health capacity. One approach is to engage in work at health-related United Nations (UN) and international organizations. However, the issue of member states underrepresentation exists, which poses a challenge both in nurturing global health experts and realizing the equitable geographical distribution prescribed in Article 101 of the United Nations Charter. Japan, among other member states, remains underrepresented in UN organizations. This study aimed to understand the job preferences of Japanese experts wishing to work at health-related international organizations and present policy proposals for strengthening capacity development and promoting international dispatch. # Methods The discrete choice experiment (DCE) survey was conducted online to determine the job preferences of health/non-health experts and students -- (i) who wished to work at health-related international organizations (*Seekers*), (ii) who are currently working at these organizations (*Workers*), and (iii) who resigned from these organizations (*Resignees*). The binary logit main effects model was used to examine the relative importance of various job attributes. # Results DCE analysis showed the relative importance of duty station, salary, work--life balance (WLB), and job satisfaction for all groups and return post and employer's contribution to welfare benefits for *Seekers* and *Resignees* but not for *Workers*. # Conclusions The "uncertainty-avoidance" characteristics mainly perceived in *Seekers* and *Resignees* propose two separate approaches, which entails supporting (i) the few selected ones, and (ii) the majority who are interested but remain uncertain and indecisive to work overseas. The social structural challenge associated with the lack of national organizations and hospitals that value experiences gained at international organizations needs to be addressed by introducing systems such as sabbatical leaves or reemployment systems for returnees. Furthermore, an incentive information package combining both financial and nonfinancial incentives focusing on favorable conditions relating to duty station, salary, WLB, and job satisfaction, which could be achieved at international organizations, could be actively publicized at career development seminars.